Prevention and Treatment of Intervertebral Disc Degeneration with Bone Marrow Derived Stem (Stromal) Cells—An in Vivo Study in Sheep. (May 2014) - Melrose, J.; Shu, C.; Dart, A.; Clarke, E. C.; Martin, J.; Bell, R.; Little, C. B.
Introduction: Intervertebral disc degeneration (IVDD) is implicated in 40% of low back pain (LBP) cases. A total of 80% of people will be affected by LBP some time in their lifetime. LBP has a considerable socioeconomic impact, costed at $100 billion in the United States in 2006 and $9.17 billion in Australia in 2001. LBP was designated a National Health Priority in Australia in 2009. Current options for the treatment of IVDD is by surgical intervention (spinal fusion) no disease modifying drug treatments are currently available. Recent studies suggest that mesenchymal stem cells (MSCs) offer therapeutic promise in IVDD, preclinical studies. In the present study, we have examined the efficacy of bone marrow derived mesenchymal stem cells (BMMSCs) for the treatment of IVDD in an ovine large animal model of IVDD. 1 Materials and Methods: A single pool of heterologous ovine BMMSCs was isolated and culture expanded up to passage 8. These BMMSCs were CD44 and CD106 +ve and CD34, CD45 and CD11b −ve by FACS analysis and capable of undergoing adipogenesis, osteogenesis, or chondrogenesis in appropriate selection medias. Disc degeneration was induced using a controlled 6 × 20 mm annular lesion in the L1L2, L3L4, and L5L6 IVDs of 3-year-old merino wethers. BMMSCs (10 million cells/0.2 mL PBS/disc) or PBS carrier (0.2 mL) were injected into the NP of these IVDs in which degeneration was induced for 4 (short- and long-term acute groups) or 12 weeks (established IVDD group) ( n = 6 sheep/group), animal sacrifice undertaken 8, 14, or 22 weeks later. The outcome measures used in this study were histology, gene profiling by qRT-PCR, biomechanical testing, and biochemical composition. The spines were also imaged by MRI and by radiography to assess changes in the IVDs. Results: A re-attainment of 90 to 95% of the prelesion disc height was evident in MSC injected but not PBS carrier injected discs. The MSC injected lesion discs also recovered their GAG contents close to those evident in age matched NOC IVDs. MSC injection either normalized or inhibited MMP2, 3, 13 or ADAMTS4 or 5 expression in all tissue zones of the lesion affected discs. Histology clearly showed a significant reduction in the propagation of the annular lesions in the MSC injected discs. Conclusion: (1) MSCs promoted repair of annular lesions and reduced degenerative IVD pathology. (2) A 90 to 95% recovery in disc heights was obtained in the MSC injected lesion discs. (3) MMP2, 3, 13, ADAMTS4, and 5 were all downregulated in lesion affected IVDs by MSC injection. (4) The GAG content of the AF and NP zones of MSC injected lesion discs were close to that of NOC IVDs at sacrifice. (5) MSCs display considerable therapeutic promise not only for the regeneration of a degenerate disc but also as a preventative measure to reduce progressive deleterious changes in established annular lesions. A potential mechanism of action of BMMSCs through modulation of metalloproteinase expression was identified. This study has shown for the first time in a large animal model relevant to the human condition that BMMSC represent a clinically relevant therapy for IVDD. Disclosure of Interest None declared Reference Melrose J, Shu C, Young C, et al. Mechanical destabilization induced by controlled annular incision of the intervertebral disc dysregulates metalloproteinase expression and induces disc degeneration. Spine 2012;37(1):18–25